Traffic noise impact on residential land planning / Walter Taimin - Taimin, Walter (2006)
In modern times, noise is recognized as a serious health problem. Annoyance caused by noise has been known since antiquity but it is only during recent times that the importance of traffic noise is taken into consideration in transport planning decisions. This study is to identify the traffic noise in Lorong Universiti A, Jalan Gasing, Petaling Jaya, Selangor. It is a residential area road that became a main road. Hence a study is required to determine the traffic noise of the road. This study also proposes the suitable solution for the road.